2022
DOI: 10.3390/nu14193917
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Branched-Chain Amino Acids on Skeletal Muscle, Glycemic Control, and Neuropsychological Performance in Elderly Persons with Type 2 Diabetes Mellitus: An Exploratory Randomized Controlled Trial

Abstract: Although branched-chain amino acids (BCAA) are known to stimulate myofibrillar protein synthesis and affect insulin signaling and kynurenine metabolism (the latter being a metabolite of tryptophan associated with depression and dementia), the effects of BCAA supplementation on type 2 diabetes (T2D) are not clear. Therefore, a 24-week, prospective randomized open blinded-endpoint trial was conducted to evaluate the effects of supplementation of 8 g of BCAA or 7.5 g of soy protein on skeletal muscle and glycemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 75 publications
(96 reference statements)
0
8
0
Order By: Relevance
“…The included study characteristics are reported in Table 3 . The studies were conducted in United States ( n = 3, [ 47 , 48 , 49 ]), Japan ( n = 3, [ 50 , 51 , 52 ]), Iran ( n = 2, [ 53 , 54 ]), Netherlands ( n = 1, [ 46 ]), China ( n = 1, [ 55 ]), and Brazil ( n = 1, [ 56 ]). In total, there were 806 participants included from studies published between 2002–2022.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The included study characteristics are reported in Table 3 . The studies were conducted in United States ( n = 3, [ 47 , 48 , 49 ]), Japan ( n = 3, [ 50 , 51 , 52 ]), Iran ( n = 2, [ 53 , 54 ]), Netherlands ( n = 1, [ 46 ]), China ( n = 1, [ 55 ]), and Brazil ( n = 1, [ 56 ]). In total, there were 806 participants included from studies published between 2002–2022.…”
Section: Resultsmentioning
confidence: 99%
“…The overall daily dose of protein varied from 0.6 g to 60 g. Most studies provided protein supplementation daily, except for Imaoka et al [ 50 , 51 ] which provided one 4.4 g dose of soy peptide drink once per week. Six studies included an exercise component of either resistance training (RT), aerobic training or both [ 47 , 50 , 51 , 52 , 54 , 56 ]. Bijeh et al [ 54 ] was the only study to include a soy only arm, and a soy + RT arm, which could be compared separately to a control (no intervention) and RT only arm, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Non-fermented whey protein supplementation was tested on muscle hypertrophy in various resistance training studies, where findings indicated that specific peptides may provide muscle recovery capabilities, while their antioxidant capacities may also contribute towards recovery physiological responses to exercise ( Devries and Phillips, 2015 ; Ha and Zemel, 2003 ; Stark et al, 2012 ). There have been several studies on the improvement of muscle parameters with whey protein supplementation ( Andersen et al, 2005 ), fermented whey proteins (FWP) on protein digestion and absorption, increment of branched chain amino acids levels, and effects of fermentation on calcium absorption and bone density improvement ( Matsuda et al, 2022 ). However, the effects of fermented whey supplementation on muscle strength and physical performance have not been investigated.…”
Section: Introductionmentioning
confidence: 99%